PUBLIC RELATIONS IN DIPONEGORO NATIONAL HOSPITAL FROM THE EXCELLENCE THEORY PERSPECTIVE - Karem Rouby Islam; Yanuar Luqman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Public relations plays a vital role in health organizations (hospitals). This study aimed to find out to what extent is the excellent public relations practiced within Diponegoro National Hospital (RSND), by analyzing the reality of public relations at Diponegoro National Hospital according to the principles of excellence theory. This study belongs to qualitative research, by relying on an in-depth interview with the public relations practitioner at Diponegoro National Hospital. Data were analyzed through some steps namely data reduction, data display, and conclusion drawing. The results of this study showed that the excellent PR is not practiced at Diponegoro National Hospital (RSND). In addition, the public relations practitioner does not participate in strategic decision-making, there is no independent PR department, and tiered communication dominates the communication process within Diponegoro National Hospital instead of a two-way symmetrical model of communication.Â